in vitro activation of complement and contact system by lactic acidosis - J. Sonntag; M. Emeis; E. Strauss; M. Obladen (Mediators of Inflammation)
The activation of complement and contact systems occurs in reperfusion injuries with initial tissue hypoxia, and lactic acidosis such as mycardial infarction and birth asphyxia. The aim of our experiment was the formal proof of activation by sole lactic acidosis. Lactic acid was added to blood and plasma samples from 10 healthy volunteers. C5a and factor XIIa were measured by EIA after incubation at 37°C for 1 h. Both concentrations increased (P<0.0001 by Friedman analysis) in blood and plasma samples with increasing amount of added lactic acid. Lactic acidosis can activate C5 from the complement system and factor XII from the contact system directly, even in the absence of cellular components.